PreCartan G-Space - Al-Sheikhly, Anmar Hashim (Al-Nahrain Journal of Science, 2018)
In this paper a preCartan G-space is our aim. Now we list the following some results that we have gotten: (i) a Cartan G-space is preCartan. (ii) We introduced some results on a net with a preopen set. (iii)We introduced this space (preCartan G-space) and give enough examples and theorems about it, where we study its properties, subspace, product, and the equivarianthomeomorphic image.